HUBUNGAN JUMLAH OBAT YANG DIRESEPKAN DENGAN POTENSIAL PENGGUNAAN OBAT YANG TIDAK TEPAT PADA PASIEN PENYAKIT GINJAL KRONIS DI RS PKU MUHAMMADIYAH YOGYAKARTA - Mulyani, Evi; Darmawan, Endang; Mustofa, Mustofa (Pharmaciana, 2015)
Age-related decrease of physiological function caused some healt problem in elderly, so the problem of treatment in the elderly is also not uncommon found as polypharmacy and Potentially Inappropriate medication (PIMs). The purpose of this study to determine the relationship of the number of drug prescribed with PIMs in elderly patients with CKD in PKU Muhammadiyah Yogyakarta Hospital. PIMs identification by STOPP criteria, while the number of drugs prescribed seen by drugs control books. To assess the patients medical history by interviews and search records. Patient characteristics were analyzed descriptively, correlations between variables were analyzed with chi square test. From 53 samples, PIMs identified 17% and average one sample got one PIMs, while of the 410 drugs that prescribed average patient receivingÂ  8 drugs (> 6). Bivariate test results showed that no significant relationship between the number of drug prescribed with PIMs.